Thermoplastic starch films reinforced with talc nanoparticles - Castillo, Luciana Andrea (2013)
Nanocomposite films of thermoplastic corn starch (TPS) with talc particles were obtained by thermo-compression in order to study the effect of filler on structure, optical, and thermal properties. Talc increased the films rigid phase, thus their cross-sections resulted more irregular. Talc preferential orientation within matrix and good compatibility between particles and TPS was observed by SEM. Slight crystalline structure changes in TPS matrix were measured by XRD and DSC, due to talc nucleating effect. Randomly dispersed talc nanoagglomerates and individual platelets were assessed by TEM. Laminar morphology and nano-sized particles allowed that nanocomposite films were optically transparent. TPS-talc films resulted heterogeneous materials, presenting domains rich in glycerol and others rich in starch. Talc incorporation higher than 3%, w/w increased softening resistance of the nanocomposites as stated by DMA. Relaxation temperatures of glycerol-rich phase shifted to higher values since talc reduces the mobility of starch chains.